Electrode material, preparation method and application

By preparing NiMn-MOF-74 and selenizing treatment, NiMn-Se electrode material was formed, which solved the problem of low conductivity of MOF electrode material, significantly improved the specific capacitance and rate performance, and improved the electrochemical performance of the supercapacitor.

CN119920637APending Publication Date: 2025-05-02XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510219665.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The low conductivity of existing MOF electrode materials limits the progress of their electrochemical reactions, resulting in lower specific capacitance, rate performance and power density, which is difficult to meet commercial applications.

Method used

By preparing NiMn-MOF-74 and selenizing treatment, a bimetallic NiMn-Se electrode material is formed, which uses the electronegative nature of selenium to improve the electron conductivity and retains the large specific surface area structural advantages of MOF.

Benefits of technology

The specific capacitance and rate performance of the electrode material is significantly improved, and the overall electrochemical performance is improved, making it more suitable for use in supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920637A_ABST
    Figure CN119920637A_ABST
Patent Text Reader

Abstract

According to the preparation method, NiMn-MOF-74 is prepared, and selenylation treatment is carried out, so that the electrode material can be obtained. Bimetal NiMn-Se is formed through the synergistic effect of selenium and NiMn-MOF-74, and the electrode material with better specific capacitance and rate capability is prepared by utilizing the structural advantage of large specific surface area of NiMn-MOF-74, higher electronic conductivity of selenide and better electronic conductivity and richer oxidation state of the nickel-manganese bimetal material. The preparation method is simple in process, easy to operate, mild in synthesis condition, rich in resource and low in cost, has universality and potential design research value, and has a wide electrochemical application prospect. The problem that an MOF electrode material is low in conductivity in the prior art is solved, and development of MOF and derivatives thereof in the field of supercapacitors is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitor electrode material preparation, specifically to an electrode material, a preparation method and an application, and in particular to a NiMn-MOF-74 derived NiMn-Se electrode material, a preparation method and an application. Background Art

[0002] As environmental pollution and energy depletion become increasingly serious, renewable resources such as solar energy, wind energy, and tidal energy have intermittent problems. Therefore, their development and utilization require low-cost, low-carbon, and environmentally friendly energy storage devices. Supercapacitors are widely used in wind power generation systems, communications, transportation, and other fields due to their fast charging and discharging speed, long cycle life, and environmental protection characteristics.

[0003] As a key factor in determining the performance of supercapacitors, the type, structure and characteristics of electrode materials have a significant impact on the performance of supercapacitors, such as capacitance, operating voltage, charge and discharge speed, and cycle life. Among them, pseudocapacitive materials use reversible reactions and near-surface Faraday reactions to store charges, showing a specific capacitance that is superior to double-layer materials. Transition metal compounds are currently the most widely studied type of pseudocapacitive electrode materials for supercapacitors due to their abundant element reserves, low prices, and outstanding capacitance performance. In addition to the chemical properties of the material itself, the microstructure of the material will also affect the capacitance performance of the electrode material. A large specific surface area can expose more active sites and greatly promote the migration rate of electrolyte ions, thereby improving the capacitance performance. Among the many pseudocapacitive electrode materials, metal-organic frameworks (MOFs) and their derivatives have become important candidates for supercapacitor electrode materials due to their excellent specific surface area, developed pore structure, and adjustable elemental composition. However, the low conductivity of MOF electrode materials will limit the progress of their electrochemical reactions, and the specific capacitance, rate performance, and power density are still low, making it difficult to meet commercial applications. Summary of the invention

[0004] In view of the problem of low conductivity of MOF electrode materials in the prior art, the present invention provides an electrode material, a preparation method and application thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing an electrode material, comprising: Preparation of NiMn-MOF-74; The NiMn-MOF-74 is subjected to selenization treatment to obtain an electrode material.

[0006] Furthermore, the method for preparing NiMn-MOF-74 is: Mixing anhydrous ethanol, N,N-dimethylformamide and deionized water to obtain a mixed solution A; Mixing nickel nitrate hexahydrate, manganese nitrate hexahydrate, salicylic acid and 2,5-dihydroxyterephthalic acid with mixed solution A to obtain mixed solution B; The mixed solution B is subjected to a solvothermal reaction to obtain NiMn-MOF-74.

[0007] Optionally, the volume ratio of anhydrous ethanol, N,N-dimethylformamide and deionized water is (1-2):(1-2):(1-2).

[0008] Optionally, the mass ratio of the nickel nitrate hexahydrate, manganese nitrate hexahydrate, salicylic acid and 2,5-dihydroxyterephthalic acid is (0.245-0.735): (0.201-0.604): (0.107-0.224): (0.0280-0.0769); in the mixed solution B, the mass concentration of nickel nitrate hexahydrate is 5.44-16.33 g / L.

[0009] Optionally, the temperature of the solvothermal reaction is 150°C to 170°C.

[0010] Optionally, the method of selenizing NiMn-MOF-74 to obtain the electrode material is: NiMn-MOF-74 and selenium powder are placed in the same space, the temperature is increased and an inert gas is introduced to obtain an electrode material.

[0011] Optionally, the mass ratio of the NiMn-MOF-74 to selenium powder is 1:(5-10).

[0012] Optionally, the specific operation of placing NiMn-MOF-74 and selenium powder in the same space, heating and introducing inert gas to obtain the electrode material is: NiMn-MOF-74 and selenium powder are placed in the same space, with NiMn-MOF-74 located downstream of the inert gas of the selenium powder. The inert gas is introduced at a rate of 40 to 80 mL / s, and the temperature is increased to 300 to 450°C at a heating rate of 3 to 5°C / min and maintained for 3 to 5 hours, and then cooled to room temperature to obtain an electrode material.

[0013] The present invention also provides an electrode material prepared by the above preparation method, wherein the specific capacitance of the electrode material reaches 3091F / g under the condition of a current density of 1A / g.

[0014] Application of the electrode materials mentioned above in supercapacitors.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing an electrode material, wherein the electrode material can be obtained by preparing NiMn-MOF-74 and performing selenization treatment. NiMn-MOF-74 is used as a precursor, and its structural advantage of large specific surface area is retained to expose more active sites and greatly promote the migration rate of electrolyte ions. At the same time, bimetallic NiMn-Se is formed through the synergistic effect of selenium and NiMn-MOF-74. The weak electronegativity of selenium gives the selenide excellent electronic conductivity, which is beneficial to the charge transfer in the electrochemical reaction process. In addition, compared with a single metal, the electrode material of bimetallic NiMn-Se has richer spin electrons, higher electronic conductivity and richer oxidation states, thereby providing higher specific capacitance and better rate performance, and improving the overall electrochemical performance of the electrode material; the preparation method is simple, the reaction conditions are mild, the equipment requirements are extremely low, the reserves of nickel and manganese elements are abundant and the price is low, the metal salts, selenium powders, etc. used are all common materials or medicines, the cost is low, and it is suitable for large-scale production, which is of great significance for promoting the development and application of MOF and its derivatives in the field of supercapacitors.

[0016] In the method for preparing NiMn-MOF-74, anhydrous ethanol, N,N-dimethylformamide and deionized water are mixed to obtain a mixed solution A; nickel nitrate hexahydrate, manganese nitrate hexahydrate, salicylic acid and 2,5-dihydroxyterephthalic acid are mixed with the mixed solution A to obtain a mixed solution B; the mixed solution B is subjected to a solvothermal reaction to obtain NiMn-MOF-74, and nitrate is selected as a metal source. Nitrate has good water solubility and organic solvent solubility, which is conducive to the uniform mixing and reaction of metal ions and organic ligands in the solvent. During the heating process, nitrate is easily decomposed to produce corresponding metal oxides or hydroxides, so as to construct the basic unit of the MOF-74 structure, and make it have a larger specific surface area and more abundant active sites, thereby providing a guarantee for the smooth progress of the electrochemical reaction.

[0017] The method for selenizing NiMn-MOF-74 to obtain an electrode material is as follows: NiMn-MOF-74 and selenium powder are placed in the same space, heated and introduced with an inert gas to obtain the electrode material; the NiMn-MOF-74 is selenized by an inert gas flow and heated to ensure uniform selenization and form bimetallic NiMn-Se, thereby achieving the purpose of improving the conductivity of NiMn-MOF-74; in addition, the moderate heating rate and selenization temperature can retain the structural advantage of the large specific surface area of ​​NiMn-MOF-74, prevent structural collapse and the occurrence of side reactions, and ensure higher activity of the material.

[0018] The present invention provides an electrode material prepared by the above preparation method. After testing, the specific capacitance of the electrode material under the condition of a current density of 1A / g reaches 3091F / g, and the electrode material has better electrochemical performance.

[0019] The application of the electrode material in supercapacitors is as follows. The supercapacitors prepared using the electrode material have the characteristics of higher energy density, faster response speed, longer service life, etc., which is of great significance for broadening the application scope of supercapacitors, promoting the development of supercapacitor technology, and promoting the progress and sustainable development of energy storage technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention is a schematic flow chart of a method for preparing an electrode material.

[0021] Figure 2 The present invention is a flow chart of a method for preparing NiMn-MOF-74 in a method for preparing an electrode material.

[0022] Figure 3 These are scanning electron microscope images of NiMn-MOF-74 prepared in an embodiment of the present invention and a scanning electron microscope image of NiMn-MOF-74 after selenization treatment, wherein a is a scanning electron microscope image of NiMn-MOF-74, and b is a scanning electron microscope image of NiMn-MOF-74 after selenization treatment in Example 3.

[0023] Figure 4 The cyclic voltammetry curves of the electrode materials prepared in Examples 1 and 3 of the present invention at a scanning rate of 20 mV / s.

[0024] Figure 5 The constant current charge and discharge curves of the electrode material prepared in the comparative example of the present invention at different current densities.

[0025] Figure 6 The constant current charge and discharge curves of the electrode material prepared in Example 1 of the present invention at different current densities.

[0026] Figure 7 The constant current charge and discharge curves of the electrode material prepared in Example 3 of the present invention at different current densities.

[0027] Figure 8 The constant current charge and discharge curves of the electrode materials prepared in the comparative example, example 1 and example 3 of the present invention under the condition of 1 A / g. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0029] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0030] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0031] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0032] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0034] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0035] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0036] See also Figure 1 The present invention provides a method for preparing an electrode material, comprising: S1: Preparation of NiMn-MOF-74, see Figure 2 , specifically: S1.1: Mix anhydrous ethanol, N,N-dimethylformamide and deionized water to obtain a mixed solution A; wherein the volume ratio of the anhydrous ethanol, N,N-dimethylformamide and deionized water is (1-2):(1-2):(1-2); S1.2: Mix nickel nitrate hexahydrate, manganese nitrate hexahydrate, salicylic acid and 2,5-dihydroxyterephthalic acid with mixed solution A to obtain mixed solution B; wherein the mass ratio of the nickel nitrate hexahydrate, manganese nitrate hexahydrate, salicylic acid and 2,5-dihydroxyterephthalic acid is (0.245-0.735): (0.201-0.604): (0.107-0.224): (0.0280-0.0769); in the mixed solution B, the mass concentration of nickel nitrate hexahydrate is 5.44-16.33 g / L; S1.3: The mixed solution B is subjected to a solvothermal reaction to obtain NiMn-MOF-74, wherein the temperature of the solvothermal reaction is 150°C to 170°C, and the time is 8 to 12 hours. After the solvothermal reaction is completed, it is alternately soaked and filtered with N,N-dimethylformamide and ethanol for 4 to 6 times, and vacuum dried at 60°C to 80°C for 10 to 14 hours.

[0037] S2: Selenization treatment is performed on NiMn-MOF-74 to obtain electrode materials, specifically: NiMn-MOF-74 and selenium powder are placed in the same space at a mass ratio of 1: (5-10), and the selenium powder is placed at the upstream end of the gas introduction, and an inert gas is introduced at a rate of 40-80 mL / s. The inert gas is one of nitrogen and argon. The temperature is increased to 300-450°C at a heating rate of 2°C-5°C / min and kept for 2-3h. Finally, the temperature is decreased to room temperature at a rate of 5°C / min to obtain an electrode material.

[0038] Comparative Example 15 mL of anhydrous ethanol, 15 mL of N,N-dimethylformamide and 15 mL of deionized water were mixed to obtain a mixed solution A; 0.245 g of nickel nitrate hexahydrate, 0.604 g of manganese nitrate hexahydrate, 0.107 g of salicylic acid and 0.0769 g of 2,5-dihydroxyterephthalic acid were added to the mixed solution A, mixed, and ultrasonically treated for 30 minutes to make the mixture uniform, to obtain a mixed solution B; The mixed solution B was transferred into a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 160 °C for 10 h. The solvothermal product was transferred to a beaker and soaked for 5 min in a small amount of N,N-dimethylformamide. The soaking solution was then filtered and rinsed alternately with N,N-dimethylformamide and methanol for 4 times each. The sample was filtered and vacuum dried at 70 °C for 12 h to obtain dry NiMn-MOF-74 powder.

[0039] Example 1 15 mL of anhydrous ethanol, 15 mL of N,N-dimethylformamide and 15 mL of deionized water were mixed to obtain a mixed solution A; 0.245 g of nickel nitrate hexahydrate, 0.604 g of manganese nitrate hexahydrate, 0.107 g of salicylic acid and 0.0769 g of 2,5-dihydroxyterephthalic acid were added to the mixed solution A, mixed, and ultrasonically treated for 30 minutes to make the mixture uniform, to obtain a mixed solution B; The mixed solution B was transferred into a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 160 °C for 10 h. The solvothermal product was transferred to a beaker and soaked for 5 min in a small amount of N,N-dimethylformamide. The soaking solution was then filtered and rinsed alternately with N,N-dimethylformamide and methanol for 4 times each. The sample was filtered and vacuum dried at 70 °C for 12 h to obtain dry NiMn-MOF-74 powder.

[0040] NiMn-MOF-74 powder and selenium powder were placed at both ends of a quartz crucible in a mass ratio of 1:5. Selenium powder was placed at the upstream end of the gas introduction. Argon gas was introduced at a rate of 80 mL / s. The temperature was increased to 350°C at a heating rate of 3°C / min and kept for 3 h. Finally, the temperature was decreased to room temperature at a rate of 5°C / min. The electrode material was recorded as NiMn-Se-5.

[0041] Example 2 15 mL of anhydrous ethanol, 15 mL of N,N-dimethylformamide and 15 mL of deionized water were mixed to obtain a mixed solution A; 0.245 g of nickel nitrate hexahydrate, 0.604 g of manganese nitrate hexahydrate, 0.107 g of salicylic acid and 0.0769 g of 2,5-dihydroxyterephthalic acid were added to the mixed solution A, mixed, and ultrasonically treated for 30 minutes to make the mixture uniform, to obtain a mixed solution B; The mixed solution B was transferred into a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 160 °C for 10 h. The solvothermal product was transferred to a beaker and soaked for 5 min in a small amount of N,N-dimethylformamide. The soaking solution was then filtered and rinsed alternately with N,N-dimethylformamide and methanol for 4 times each. The sample was filtered and vacuum dried at 70 °C for 12 h to obtain dry NiMn-MOF-74 powder.

[0042] NiMn-MOF-74 powder and selenium powder were placed at both ends of a quartz crucible in a mass ratio of 1:6. Selenium powder was placed at the upstream end of the gas introduction. Argon gas was introduced at a rate of 80 mL / s. The temperature was increased to 350°C at a heating rate of 3°C / min and kept for 3 h. Finally, the temperature was decreased to room temperature at a rate of 5°C / min. The electrode material was recorded as NiMn-Se-6.

[0043] Example 3 15 mL of anhydrous ethanol, 15 mL of N,N-dimethylformamide and 15 mL of deionized water were mixed to obtain a mixed solution A; 0.245 g of nickel nitrate hexahydrate, 0.604 g of manganese nitrate hexahydrate, 0.107 g of salicylic acid and 0.0769 g of 2,5-dihydroxyterephthalic acid were added to the mixed solution A, mixed, and ultrasonically treated for 30 minutes to make the mixture uniform, to obtain a mixed solution B; The mixed solution B was transferred into a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 160 °C for 10 h. The solvothermal product was transferred to a beaker and soaked for 5 min in a small amount of N,N-dimethylformamide. The soaking solution was then filtered and rinsed alternately with N,N-dimethylformamide and methanol for 4 times each. The sample was filtered and vacuum dried at 70 °C for 12 h to obtain dry NiMn-MOF-74 powder.

[0044] NiMn-MOF-74 powder and selenium powder were placed at both ends of a quartz crucible in a mass ratio of 1:7. Selenium powder was placed at the upstream end of the gas introduction. Argon gas was introduced at a rate of 80 mL / s. The temperature was increased to 350°C at a heating rate of 3°C / min and kept for 3 h. Finally, the temperature was decreased to room temperature at a rate of 5°C / min. The electrode material was recorded as NiMn-Se-6.

[0045] Example 4 18 mL of anhydrous ethanol, 12 mL of N,N-dimethylformamide and 15 mL of deionized water were mixed to obtain a mixed solution A; 0.365 g of nickel nitrate hexahydrate, 0.42 g of manganese nitrate hexahydrate, 0.157 g of salicylic acid and 0.03 g of 2,5-dihydroxyterephthalic acid were added to the mixed solution A, mixed, and ultrasonically treated for 30 minutes to make the mixture uniform, to obtain a mixed solution B; The mixed solution B was transferred into a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 170 °C for 8 h. The solvothermal product was transferred to a beaker, and a small amount of N,N-dimethylformamide was added to soak for 5 min. The soaking solution was then filtered and the sample was rinsed alternately with N,N-dimethylformamide and methanol for 6 times each. The sample was filtered and vacuum dried at 60 °C for 13 h to obtain dry NiMn-MOF-74.

[0046] NiMn-MOF-74 and selenium powder were placed at both ends of a quartz crucible in a mass ratio of 1:8. Selenium powder was placed at the upstream end of the gas. Argon was introduced at a rate of 40 mL / s. The temperature was increased to 400°C at a heating rate of 4°C / min and kept for 3 h. Finally, the temperature was decreased to room temperature at a rate of 5°C / min. The electrode material was recorded as NiMn-Se-8.

[0047] Example 5 13 mL of anhydrous ethanol, 23 mL of N,N-dimethylformamide and 9 mL of deionized water were mixed to obtain a mixed solution A; 0.735 g of nickel nitrate hexahydrate, 0.201 g of manganese nitrate hexahydrate, 0.224 g of salicylic acid and 0.0664 g of 2,5-dihydroxyterephthalic acid were added to the mixed solution A, mixed, and ultrasonically treated for 30 minutes to make the mixture uniform, to obtain a mixed solution B; The mixed solution B was transferred into a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 150 °C for 12 h. The solvothermal product was transferred to a beaker, and a small amount of N,N-dimethylformamide was added to soak for 5 min. The soaking solution was then filtered and the sample was rinsed alternately with N,N-dimethylformamide and methanol for 6 times each. The sample was filtered and dried at 50 °C in vacuum for 14 h to obtain dry NiMn-MOF-74.

[0048] NiMn-MOF-74 and selenium powder were placed at both ends of a quartz crucible in a mass ratio of 1:9. Selenium powder was placed at the upstream end of the gas. Argon was introduced at a rate of 70 mL / s. The temperature was increased to 450°C at a rate of 5°C / min and kept for 3 hours. Finally, the temperature was decreased to room temperature at a rate of 5°C / min. The electrode material was recorded as NiMn-Se-9.

[0049] Example 6 12 mL of anhydrous ethanol, 12 mL of N,N-dimethylformamide and 21 mL of deionized water were mixed to obtain a mixed solution A; 0.463 g of nickel nitrate hexahydrate, 0.426 g of manganese nitrate hexahydrate, 0.182 g of salicylic acid and 0.0462 g of 2,5-dihydroxyterephthalic acid were added to the mixed solution A, mixed, and ultrasonically treated for 30 minutes to make the mixture uniform, to obtain a mixed solution B; The mixed solution B was transferred into a 100 mL polytetrafluoroethylene reactor for solvothermal reaction at 160 °C for 12 h. The solvothermal product was transferred to a beaker, and a small amount of N,N-dimethylformamide was added to soak for 5 min. The soaking solution was then filtered, and the sample was repeatedly rinsed with N,N-dimethylformamide and methanol alternately for 6 times each, filtered, and vacuum dried at 80 °C for 10 h to obtain dry NiMn-MOF-74.

[0050] NiMn-MOF-74 and selenium powder were placed at both ends of a quartz crucible in a mass ratio of 1:10. Selenium powder was placed at the upstream end of the gas. Argon was introduced at a rate of 80 mL / s. The temperature was increased to 300°C at a rate of 5°C / min and kept for 5 h. Finally, the temperature was decreased to room temperature at a rate of 5°C / min. The electrode material was recorded as NiMn-Se-10.

[0051] See also Figure 3 It can be seen that the NiMn-MOF-74 prepared in the comparative example is in the shape of a tremella ball and nanograss of about 2 μm, showing a large specific surface area. The scanning electron microscope image of the NiMn-MOF-74 after selenization treatment in Example 1, that is, the electrode material NiMn-Se-5 prepared in Example 1, basically maintains the morphology of NiMn-MOF-74, is in the shape of a tremella ball of about 2 μm, and has a large number of active sites on the surface.

[0052] The electrode materials prepared in the comparative example and examples 1-3 were respectively mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 16:3:1 in ethanol to form a uniform slurry, applied onto a 1cm*1cm nickel foam, and used as a working electrode after drying. A platinum electrode and a saturated calomel electrode were used as an auxiliary electrode and a reference electrode, respectively, and 6 mol / L KOH was used as an electrolyte. The electrochemical properties under three electrodes were tested on a Coster electrochemical workstation.

[0053] See also Figure 4 The cyclic voltammetry curves of the electrodes prepared in the comparative example and Examples 1 and 3 at 20 mV / s show clear redox peaks, proving their pseudocapacitive properties. Compared with the NiMn-MOF-74 in the comparative example, Examples 1 and 3 show stronger redox peaks, indicating higher electrochemical activity and better supercapacitive performance. See also Figure 5, from the constant current charge and discharge curves of the electrode material prepared in the comparative example at different current densities, it can be seen that the GCD curves at different current densities are highly symmetrical, which shows that the prepared material has excellent coulombic efficiency and excellent electrochemical reversibility. It is calculated that the specific capacitance of the electrode material at current densities of 1A / g, 2A / g, 5A / g, 10A / g and 20A / g is 2192 F / g, 1817.8 F / g, 1559 F / g, 1272.7 F / g and 928 F / g respectively.

[0054] See also Figure 6 It can be seen from the GCD curves of the electrode material NiMn-Se-5 prepared in Example 1 at different current densities that the GCD curves at different current densities are highly symmetrical, which shows that the prepared material has excellent coulombic efficiency and excellent electrochemical reversibility. According to calculations, the specific capacitance of the electrode material at current densities of 1A / g, 2A / g, 5A / g, 10A / g and 20A / g is 2748.8 F / g, 2300 F / g, 1820 F / g, 1576.6F / g and 1160 F / g, respectively.

[0055] See also Figure 7 It can be seen from the GCD curves of the electrode material NiMn-Se-7 prepared in Example 3 at different current densities that the GCD curves at different current densities are highly symmetrical, which shows that the prepared material has excellent coulombic efficiency and excellent electrochemical reversibility. It is calculated that the specific capacitance of the electrode material at current densities of 1A / g, 2A / g, 5A / g, 10A / g and 20A / g is 3091 F / g, 2399 F / g, 1848 F / g, 1453 F / g and 1276 F / g, respectively.

[0056] See also Figure 8 It can be seen from the GCD curves of the electrode materials of the comparative example, Examples 1 and 3 at a current density of 1 A / g that the constant current charge and discharge curves all present a highly symmetrical charge and discharge platform, which is consistent with the CV curve results. This shows that the prepared materials have excellent coulombic efficiency and outstanding electrochemical reversibility. NiMn-Se-7 has the longest charge and discharge time, which is also consistent with the strongest redox peak result of the CV curve.

[0057] In summary, the present invention provides an electrode material, a preparation method and an application. The electrode material can be obtained by preparing NiMn-MOF-74 and performing selenization treatment. Taking advantage of the structural advantage of the large specific surface area of ​​the MOF material, the NiMn-Se prepared with the prepared NiMn-MOF-74 as a precursor also retains a large specific surface area, which can provide abundant active sites for electrochemical reactions and achieve full contact with the electrolyte; the weak electronegativity of selenium gives the selenide excellent electronic conductivity, which is beneficial to the charge transfer during the electrochemical reaction; in addition, compared with a single metal, the nickel-manganese bimetallic material has better electronic conductivity and richer oxidation states, thereby providing higher specific capacitance and better rate performance, improving the overall electrochemical performance of the electrode material, and promoting the development of MOF and its derivatives in the field of supercapacitors.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A method for preparing an electrode material, characterized in that: include: Preparation of NiMn-MOF-74; The NiMn-MOF-74 is subjected to selenization treatment to obtain an electrode material.

2. The method for preparing an electrode material according to claim 1, characterized in that: The method for preparing NiMn-MOF-74 is: Mixing anhydrous ethanol, N,N-dimethylformamide and deionized water to obtain a mixed solution A; Mixing nickel nitrate hexahydrate, manganese nitrate hexahydrate, salicylic acid and 2,5-dihydroxyterephthalic acid with mixed solution A to obtain mixed solution B; The mixed solution B is subjected to a solvothermal reaction to obtain NiMn-MOF-74.

3. The method for preparing the electrode material according to claim 2, characterized in that: The volume ratio of the anhydrous ethanol, N,N-dimethylformamide and deionized water is (1-2): (1-2): (1-2).

4. The method for preparing an electrode material according to claim 2, characterized in that: The mass ratio of the nickel nitrate hexahydrate, manganese nitrate hexahydrate, salicylic acid and 2,5-dihydroxyterephthalic acid is (0.245-0.735): (0.201-0.604): (0.107-0.224): (0.0280-0.0769); in the mixed solution B, the mass concentration of nickel nitrate hexahydrate is 5.44-16.33 g / L.

5. The method for preparing an electrode material according to claim 2, characterized in that: The temperature of the solvent thermal reaction is 150°C to 170°C.

6. The method for preparing an electrode material according to claim 1, characterized in that: The method of selenizing NiMn-MOF-74 to obtain the electrode material is as follows: NiMn-MOF-74 and selenium powder are placed in the same space, the temperature is increased and an inert gas is introduced to obtain an electrode material.

7. The method for preparing an electrode material according to claim 6, characterized in that: The mass ratio of the NiMn-MOF-74 to selenium powder is 1:(5-10).

8. The method for preparing an electrode material according to claim 6 or 7, characterized in that: The specific operation of placing NiMn-MOF-74 and selenium powder in the same space, heating and introducing inert gas to obtain the electrode material is as follows: NiMn-MOF-74 and selenium powder are placed in the same space, with NiMn-MOF-74 located downstream of the inert gas of the selenium powder. The inert gas is introduced at a rate of 40 to 80 mL / s, and the temperature is increased to 300 to 450°C at a heating rate of 3 to 5°C / min and maintained for 3 to 5 hours, and then cooled to room temperature to obtain an electrode material.

9. An electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The specific capacitance of this electrode material reaches 3091F / g at a current density of 1A / g.

10. Use of the electrode material according to claim 9 in a supercapacitor.